2023
DOI: 10.1186/s40560-023-00660-9
|View full text |Cite
|
Sign up to set email alerts
|

Onset timing and duration of augmented renal clearance in a mixed intensive care unit

Abstract: Background Augmented renal clearance (ARC) is associated with lower blood plasma concentrations of renally excreted drugs; however, its time course is unknown. The current study aimed to determine the onset timing/duration of ARC, its risk factors, and its association with clinical outcomes by continuous monitoring of urinary creatinine clearance (CrCl) in critically ill patients. Methods Data were retrospectively obtained from the medical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A study found that the overall prevalence of ARC in patients older than 18 years was as high as 24.6%. 12,28 The risk factors for the occurrence of ARC are also including trauma, young age, and male sex which were exist in this patient. 11 Another multivariate analysis identified younger age, male sex, lower serum creatinine at admission, admission with central nervous system disease, no medical history, use of mechanical ventilation, and use of vasopressor as onset factors for ARC.…”
Section: Dovepressmentioning
confidence: 77%
See 2 more Smart Citations
“…A study found that the overall prevalence of ARC in patients older than 18 years was as high as 24.6%. 12,28 The risk factors for the occurrence of ARC are also including trauma, young age, and male sex which were exist in this patient. 11 Another multivariate analysis identified younger age, male sex, lower serum creatinine at admission, admission with central nervous system disease, no medical history, use of mechanical ventilation, and use of vasopressor as onset factors for ARC.…”
Section: Dovepressmentioning
confidence: 77%
“…11 Another multivariate analysis identified younger age, male sex, lower serum creatinine at admission, admission with central nervous system disease, no medical history, use of mechanical ventilation, and use of vasopressor as onset factors for ARC. 12 This patient had several risk factors including younger age, male sex, vasopressor use and use of mechanically assisted ventilation. For ARC patients exposed to β-lactam antibiotics, the drug concentration is easily lower than the therapeutic target.…”
Section: Dovepressmentioning
confidence: 98%
See 1 more Smart Citation
“…In critically ill patients with cancer ARC development on the first day of intensive care unit (ICU) admission demonstrated a significant association with younger age (OR 1.028, 95% CI: 1.005–1.051) [ 264 ]. Despite the association with young age stated above a retrospective study of 2592 critically ill patients admitted to the ICU revealed that the median age of patients with ARC was 70 (55–79) years, with a prevalence of 33.4% [ 265 ], pointing out the importance of the ARC for the elderly population. This state can lead to decreased AB exposure and thus to treatment failure with beta-lactams, aminoglycosides, glycopeptides, and other, mainly hydrophilic agents [ 262 ].…”
Section: General Considerations On Ab Pharmacokinetics In the Elderlymentioning
confidence: 99%
“…Augmented Renal Clearance (ARC), most commonly defined as a glomerular filtration rate (GFR) of >130 mL/min/1.73 m 2 [ 1 ], is a phenomenon of increased renal clearance of circulating solutes that has received increasing attention due to its negative effects of inadequate drug exposure, poor efficacy, and the increased risk of resistant bacteria [ 2 , 3 ]. ARC often occurs in critically ill people with ailments such as burns, sepsis, cancer, multiple injuries, and subarachnoid hemorrhaging [ 4 , 5 , 6 , 7 ]. ARC has also been reported in patients with coronavirus disease 2019 (COVID-19) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%